The effect of using different extraction technique towards the quality of Piper betel crude extract / Muhammad Hurayth Sabran Mohd Hanafi - Mohd Hanafi, Muhammad Hurayth Sabran (2023)
Piper betel or widely known as Daun Sireh has been widely used traditionally to treat various disease since ancient time. Its therapeutic properties such as antibacterial, anti- inflammatory and antioxidant activities was believed to be contributed by its bioactive compounds. The extracting solvent is crucial to extract its bioactive compound which contribute to its therapeutic activities. The effects of various solvents on the antioxidant and antibacterial activity of Piper Betel leaf extract have not been well studied. Therefore, this study was conducted to determine the effect of using different types of technique (maceration and Soxhlet) towards the percentage of extraction yield and the amount of Gallic acid in Piper betel leaf crude extract. The extraction of Piper betel leaf was done by using maceration and Soxhlet extraction technique and the determination and quantification of Gallic acid was implemented by using High Performance Liquid Chromatography (HPLC). The result showed that the percentage of extraction yield was ranging from 1% - 55 %. The highest percentage extraction yield was exhibited by Soxhlet with the value of 55%. Furthermore, all extract showed the presence of Gallic acid with the range of 20ppm-48ppm. The highest value of Gallic acid was exhibited by the extraction using maceration as a technique which is 48.28ppm. Therefore, the extraction of Piper betel leaf using maceration was chosen as the best extraction technique to extract Gallic acid and has a potential to be developed as a future herbal-based products. In a nutshell, the extracting technique method which are maceration and Soxhlet gives a significant effect on the percentages of extraction yield and the amount of Gallic acid presence in the Piper betel leaf crude extract.